Implementasi pasal 95 UU No 1 Tahun 2011 tentang Perumahan dan Kawasan Permukiman di Kawasan Barito Kota Semarang - A., Wahyu Pradana; Widowati, Nina (Journal of Public Policy and Management Review, 2016)
This research aims to describe implementation article 95 of law no. 1 year 2011 About Housing and the premukiman in the area of the Barito Semarang city and to know the factors that hinder the implementation of article 95 of law No. 1 of 2011. Locus was used in this research is in the area of JL. Barito Camel City Of Semarang. This research uses qualitative research methods are descriptive. Implementation of article 95 of law no. 1 year 2011 About housing and residential areas in the region of the Barito Semarang city still encountered obstacles. Factors restricting implementation include: factors of poverty, low level of employment, the most expensive place to live, there is a group of people that rule the slum areas or wild. Conclusions in this study are implementation article 95 of law no. 1 year 2011 About Housing and the premukiman in the area of the Barito Semarang city, still encountered obstacles primarily viewed from many residents who still live in the wild, the existence of a settlement of a pile of garbage that exist around the settlements of the wild and the existence of illegal karaoke. Based on these conclusions, the researchers recommend to the Government in order to provide training to the residents of the settlement of wild creativity to be able to work mengasilkan that can be used as income.